Studi Analisis Pengaruh Perubahan Posisi Nozzle Terhadap Pout Pada Prototipe PLTMH - Kristama, Daniel; Weking, Antonius Ibi; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 17 No 2 (2018): (May - Agustus) Majalah Ilmiah Teknologi Elektro, 2018)
Renewable sources of energy by utilizing water resources, more specifically is PLTMH (Micro-Hydro power plants) to be an excellent choice for potential to be developed in order to overcome the scarcity of energy. For ease in learning about PLTMH then use PLTMH prototype by designing the nozzle position on the corner of 0 0 , 15 0 , 30 0 , 45 0 , 60 0 and 75 0 to measurements, using three types of turbine vanes, on the position of the nozzle at an angle of 60 0 produces round generator and turbine rotation. The position of the nozzle at an angle of 60 0 , a model turbine vanes are recommended to be used is semicircular vanes model because the model in the position and the power-generating turbine vanes most large.